THE EFFECT OF CAPITAL STRUCTURE, FIXED ASSET INTENSITY AND COMPANY SIZE ON CORPORATE INCOME TAX PAYABLE - Siti Khurotul Aini; Dwi Septiani (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of capital structure, fixed asset intensity, and company size on corporate income tax payable in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. The method used is a quantitative method with secondary data from the financial statements of consumer non-cyclicals sector companies listed on the IDX in the period. This study applied a purposive sampling technique, which resulted in 31 companies over six years with a total of 186 observations. The data was analyzed using EViews 12 software. The results of the study show that: (1) Capital structure, fixed asset intensity, and company size simultaneously affect the income tax of payable entities; (2) Capital structure affects the income tax of the payable entity; (3) The intensity of fixed assets has no effect on the income tax of the payable entity; (4) The size of the company affects the income tax of the payable entity.